Dari Nusantara ke Patani: Evolusi Peradaban Islam dalam Lanskap Budaya Asia Tenggara - Duski Ibrahim; Hendri Faroza; Agus Srimudin; Dyan Dwianty (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2026)
This study aims to analyze the evolution of Islamic civilization within the cultural landscape of Southeast Asia through a comparative study between Indonesia and Patani, Thailand. The research employs a qualitative approach with a comparative case study design based on literature review, examining the historical, social, cultural, and political developments of both regions. The findings reveal that the development of Islamic civilization in Indonesia occurred through an inclusive and adaptive process of cultural acculturation. Islamic values were integrated with local traditions, creating a moderate and harmonious religious pattern within society. In contrast, the development of Islam in Patani took place under conditions of political marginalization and state pressure, which fostered cultural resistance and strengthened the religious identity of the Malay Muslim community. These differences indicate that socio-political structures play a significant role in shaping the dynamics of Islamic civilization. The study confirms that Islam as a civilization is flexible and adaptable to different cultural environments; however, the form of adaptation is strongly influenced by power relations, social conditions, and local political contexts. This research is expected to enrich the study of Islamic civilization in Southeast Asia through a comparative approach that integrates cultural and political dimensions more comprehensively.